2014
DOI: 10.1073/pnas.1317488111
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic cleavage of Ser52Pro variant transthyretin triggers its amyloid fibrillogenesis

Abstract: The Ser52Pro variant of transthyretin (TTR) produces aggressive, highly penetrant, autosomal-dominant systemic amyloidosis in persons heterozygous for the causative mutation. Together with a minor quantity of full-length wild-type and variant TTR, the main component of the ex vivo fibrils was the residue 49-127 fragment of the TTR variant, the portion of the TTR sequence that previously has been reported to be the principal constituent of type A, cardiac amyloid fibrils formed from wild-type TTR and other TTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
151
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(164 citation statements)
references
References 26 publications
12
151
1
Order By: Relevance
“…Previous in vitro studies [21,22] have provided evidence that RBP4 can extend the aggregation kinetics of thermally-denatured TTR, implying that RBP4 stabilizes the native conformation of TTR. Based on these findings, we theorized that TTR found in amyloid deposits would no longer be bound to its natural and stabilizing binding partner, RBP4.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies [21,22] have provided evidence that RBP4 can extend the aggregation kinetics of thermally-denatured TTR, implying that RBP4 stabilizes the native conformation of TTR. Based on these findings, we theorized that TTR found in amyloid deposits would no longer be bound to its natural and stabilizing binding partner, RBP4.…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis, the various structural domains, cleavage sites and a few selected key mutations in hTTR are shown schematically in Figure 1. The above single monomeric chain forms a strong tetrameric complex (Calculated MW ~55,044 Da) that exhibits its physiological and biological activity [33][34][35]. A recent study with hTTR wild type as well as its key physiological mutant variants suggested that each monomeric form of hTTR is proteolytically cleaved likely by a trypsin like enzyme and this site may be located not far from 50 amino acids from the N-terminal end.…”
Section: Peptide Designmentioning
confidence: 99%
“…A more recent study revealed that for both wild type and variant hTTR, a significantly high level of hTTR (49-127) fragment was found to be present in ex vivo fibril aggregates along with only a small quantity of full length proteins [33]. Moreover the above hTTR sequence domain has also been reported to be the major constitutent of wild type and hTTR variants derived amyloid fibrils linked to cardiomyopathy [34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations